2005
DOI: 10.1016/j.nuclcard.2005.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hormone replacement on myocardial fatty acid metabolism: Potential role of estrogen

Abstract: In postmenopausal women, estrogen use is associated with increased myocardial fatty acid utilization. Thus, when the cardiac effects of hormone replacement therapy are being assessed, alterations in myocardial substrate metabolism should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 37 publications
2
22
0
Order By: Relevance
“…As a result, cellular ATP levels were reduced and the activation status of AMP-Kα, which can regulate that activity of Runx2 (21), was increased. Estrogen favors fatty acid metabolism in a number of tissues (39)(40)(41)(42) and may therefore prevent the switch to glycolytic metabolism in osteoblasts. This idea is worthy of additional study and will likely require the use of models in which estrogen receptor signaling has been modified in the osteoblast lineage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, cellular ATP levels were reduced and the activation status of AMP-Kα, which can regulate that activity of Runx2 (21), was increased. Estrogen favors fatty acid metabolism in a number of tissues (39)(40)(41)(42) and may therefore prevent the switch to glycolytic metabolism in osteoblasts. This idea is worthy of additional study and will likely require the use of models in which estrogen receptor signaling has been modified in the osteoblast lineage.…”
Section: Discussionmentioning
confidence: 99%
“…We speculated that the more severe defect in in vitro maturation induced by E2 treatment of ΔCpt2 osteoblast might be due to an inability to adjust fuel selection, since E2 favors fatty acid utilization in a number of tissues (39)(40)(41)(42). To test this idea, control and ΔCpt2 osteoblast cultured in the presence or absence of E2 were labeled with 2-deoxy-D-[ Figure 3G), suggestive of an adjustment in cellular metabolism to maintain ATP levels.…”
Section: Skeletal Accumulation Of Fatty Acidsmentioning
confidence: 99%
“…We presumed that estrogen had a key modulator role in lipid metabolism. Herrero et al reported that myocardial fatty acid utilization was higher in women taking estrogens compared to those not receiving estrogens, which might be attributable to the regulation of β-oxidation of fatty acids [39] . It has been reported that mRNA expression and the activity of enzymes including medium-chain acyl coenzyme A dehydrogenase and acetyl CoA oxidase, enzymes with fatty acid β-oxidation, are reduced under estrogen deficiency [40] .…”
Section: Discussionmentioning
confidence: 99%
“…This gender-related difference may be a result of the fact that, in hearts from females, glucose metabolism may be decreased during ischemia because of substrate competition, as a result of a greater fatty acid delivery to the myocardium. A trend towards higher myocardial use of fatty acids was noted retrospectively in women taking estrogens when compared with untreated women (22).…”
Section: Discussionmentioning
confidence: 93%
“…This would be consistent with a greater depletion of glycogen stores in hearts from females relative to males when preserved in this cardioplegic solution. Female hearts are characterized by a greater myocardial blood flow (22,23), which leads to higher cardiac work and oxygen consumption, lower efficiency and lower fasting myocardial glucose utilization. Greater myocardial blood flow also tends to be associated with greater myocardial fatty acid utilization and oxidation (24,25).…”
Section: Discussionmentioning
confidence: 99%